Factors associated with household flood preparedness in Songkhla old town Thailand - Srijya Thapa; Yusuke Toyoda; Orapin Laosee; Piyapong Janmaimool; Tarinee Buadit; Nattaneeporn Noisangiam; Cheerawit Rattanapan (Progress in Disaster Science)
This study investigates household disaster preparedness in Songkhla Old Town, Thailand, a culturally significant area vulnerable to floods. Using the Protection Motivation Theory framework, we conducted a cross-sectional survey of 450 households to assess preparedness levels and identify associated factors. Our findings revealed that disaster preparedness knowledge emerged as the strongest predictor of household preparedness (β = 0.539, p < 0.001), followed by perceived disaster risk (β = 0.202, p < 0.001) and perceived disaster consequences (β = 0.193, p < 0.001). Community preparedness and support (β = 0.134, p < 0.001) and governmental preparedness (β = 0.126, p = 0.003) also positively influenced preparedness behaviors, while anxiety showed a negative relationship (β = −0.124, p = 0.010). Notably, socio-demographic characteristics did not significantly predict preparedness, suggesting the importance of local cultural and institutional context. These findings underscore the need for multi-faceted interventions integrating individual-level factors like knowledge with community-level factors like social cohesion and governmental support.